(untitled) (Journal of Pedagogical Inventions and Practices, 2024)
STELLARIUM measured the results on June 22 and December 21-22 using a protractor or theodolite in the open sky for 24 hours. Of course, the results of practical measurements of students, schoolchildren and young astronomers leave a deep memory in them